Genprofilirovanie energoobespecenija u sportsmenov vysokoj kvalifikacii na primere biatlona - Krucinskij, N.G.; Lebed, T. L.; Marinic, V. V.; Sliz, A. A.; Šepeleviv, N. V.; Evdoljuk S. V. (Zdorov'e dlja vsech, 2018)
In the presented article, the possibilities of carrying out the gene-profiling of the power supply process on the example of biathlon are considered. The results of typing of 31 biathlon-athletes of high qualification on a panel of 6 polymorphic markers of the carbohydrate-lipid metabolism genes involved in energy supply processes (ACE, PPARA, PPARGC1A, PPARD, PPARGC1B and PPARG2) are given. The study was conducted in compliance with the necessary ethical criteria: obtaining informed consent from athletes, ensuring the confidentiality of personal information. In the examined group of biathlon-athletes the prevalence of the frequency of genotypes DD (45.16%) and ID (45.16%) and allele D (67.74%) of the ACE gene, genotype GG (64.52%) and allele G (77.42%) of the gene PPARA, the genotype GlySer (80.64%) and the Ser-allele (56.45%) of the PPARGC1A gene, the TT genotype (54.84%) and the T allele (74.20%) of the PPARD gene, the CC (90,32) allele C (95.16%) of the gene PPARG2, genotype CC (100.00%) and allele C (100.00%) of the gene PPARGC1B. The results of the DNA survey showed quite effective energy supply for this group of athletes, which is quite understandable for their high level of sports qualification. Establishing the genetic potential of each athlete allows you to determine or refine the molecular mechanisms of inheritance and expand the theoretical and methodological basis of the process of sports training. At the same time, having determined the differences in the distribution of genotypes in groups of highly qualified athletes engaged in various sports, it is possible to carry out with confidence the genetic prognosis of success in the group of reserve athletes. Based on the results of earlier conducted own research, analysis of the world experience, an algorithm for managing the selection process of the reserve group athletes and subsequent optimization of their training process is proposed.